KAJIAN KELAYAKAN KEGIATAN PERTAMBANGAN BAHAN GALIAN GOLONGAN C DI KECAMATAN CEPOGO KABUPATEN BOYOLALI - Najib Najib; Junaedi Junaedi (TEKNIK, 2009)
Sand and Gravel mining activity in Cepogo District come out pro and contra in that society. This researchaims to figure out the impact of mining from physical aspect. Parameters used in this research such ascondition and mining activity, hydrology, erosion, land exchanged, infrastructure condition, mass wasting,land use and reclamation effort. From those parameters are counted mining properness in those locations.According with data analysis, mining activity in eight villages in Cepogo District has improper mining(e.g. Gedangan, Sumbung, Paras, Mliwis, Sukabumi, Cepogo and Cabean Kunthi) and in one location isvery improper mining (Wonodoyo). This condition due to mining didn’t follow good mining practice(GMP).